Association between Cytochrome P450 1B1 (rs1056836), C-C Chemokine Receptor Type 2 (rs1799864), and Monocyte Chemoattractant Protein-1 (rs1163763) Gene Polymorphism and Head-and-neck Cancer and Oral Squamous Cell Carcinoma Risk: A Systemic Review and Meta-analysis - Bibin Savio Antony; Prabhu Manickam Natarajan; Veerakumar Ramachandran; Gowtham Kumar Subbaraj (Journal of Head & Neck Physicians and Surgeons)
This study aimed to validate a potential link between gene polymorphic variations in cytochrome P450 1B1 (CYP1B1; rs1056836), C-C chemokine receptor type 2 (CCR2; rs1799864), monocyte chemoattractant protein-1 (MCP-1; rs1163763) and the development of head-and-neck cancer (HNSCC), and oral squamous cell carcinoma (OSCC). A meticulous search strategy was used to find pertinent case–control studies. The required data were retrieved from the major databases: PubMed, Scopus, Embase, and Google Scholar. The search queries were used in combination with the term “OSCC,” “HNSCC,” “head and neck cancer” and “Oral Squamous Cell Carcinoma,” “gene polymorphism,” and “CYP1B1 (rs1056836), CCR2 (rs1799864), and MCP-1 (rs1163763).” Based on the requirements for this meta-analysis, we selected 11 articles out of 130. Through the present meta-analysis, a strong correlation between variations in the gene CYP1B1 (rs1056836) and association with HNSCC susceptibility was identified and also was reported that CCR2 (rs1799864) and MCP-1 (rs1163763) do not have a link with OSCC development in Asian and Caucasian population. OSCC risk has been investigated in relation to three different gene variants. However, there was a possible correlation with CYP1B1 (rs1056836). Additional research with larger and more different populations is necessary since MCP-1 (rs1163763) revealed a potential association in one genetic model. However, more studies are needed to confirm these results.